Deux patriarcats différents ? Une « dispute entre sœurs » au sein du féminisme allemand au moment de la « réunification » des deux États allemands - Cornelia Möser (Genre & Histoire)
In analyzing the difficult meeting between West and East German feminists following “reunification” in the early 1990s, this article hopes to contribute to a better understanding of the dynamics of gender and the sexual politics in the partitioned history of Germany. The article explores the variety of uses of “identity” (Identität), “equality” (Gleichheit) and “difference” (Differenz) in feminist discourse in the East and in the West, and in the process questions the validity of the dominant understanding of feminism in Germany : seeing West German feminism as based on difference, whereas East German feminism is supposed to be based on claims of equality. For some, these supposedly different base assumptions were the reason for the failed encounter between feminists from the East and West in the years following “reunification”. Yet the notions of difference and equality are to be found in feminist texts and speech in both the West and the East. Moreover, the fall of the Berlin wall coincided with the feminist gender debate in Germany : the debate on a philosophy of difference also helped to put on a name on the differences between the East and the West.